Cross-border traders: emerging, multiple and shifting identities - Muzvidziwa, Victor N. (CSSALL Publishers, 2016)
A significant number of Zimbabweans cross borders daily to engage in informal cross-border trade. Zimbabwean cross-border traders are a ‘cosmopolitan, footloose group of cultural and economic entrepreneurs’. They are a highly gendered group, as they comprise mostly women. These women cross-border traders are characterised by emergent, multiple, shifting and negotiated identities. In Zimbabwe, cross-border trade as an occupation had given rise to the image of a strong, independent and mobile class of women involved in long distance transborder business (Cheater 1998; Muzvidziwa 1999, 2000 and 2005; and Zinyama 2000). A new identity marking women cross-border traders from others appeared to be emerging. The paper draws largely from the one year study by the author in 2002 in Chinhoyi, the capital of Mashonaland West Province and Harare, Zimbabwe’s capital. This paper seeks to examine how identity is formed and legitimated in the context of women cross border’s lived experiences. The paper examines issues related to emerging, shifting and multiple identities in the context of cross border trade. The paper focuses mostly on lived experiences of Zimbabwean crossborder traders. Global domains and issues concerning home and belonging and acquired cross-border identities are also examined in the paper. Discussions in this paper lead to the conclusion that anthropological perspectives are useful and do contribute to a better understanding of issues of belonging and identity among cross border traders in Zimbabwe today.